2014
DOI: 10.1016/j.apsb.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the study of (–)clausenamide: chemistry, biological activities and mechanism of action

Abstract: Clausenamide (clau) is one of seven novel compounds isolated from Clausena lansium (Lour) skeels. Clau is unusual in that it contains 4 chiral centers yielding 8 pairs of enantiomers. After identification of the configuration of these enantiomers, the synthesis of 16 enantiomers, including optically active clau and (+) and (–)clau was carried out. During this study, many stereochemical and synthetic difficulties were solved and the Baldwin principle was updated. Production scale is now sufficient to meet the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Clausenamide (Clau) is a newly found alkaloid that is isolated from the leaves of Clausena lansium (Lour) Skeels, and an evaluation of its activity showed that the principal pharmacological effects of (-)-Clau were to increase the cognition of mice/rats and inhibit, to different degrees, the pathological changes of AD through its multi-target effects [9,10]. Claulansine F (Clau F) is a new carbazole alkaloid isolated from the stem of C. lansium (Lour) Skeels [11].…”
Section: Introductionmentioning
confidence: 99%
“…Clausenamide (Clau) is a newly found alkaloid that is isolated from the leaves of Clausena lansium (Lour) Skeels, and an evaluation of its activity showed that the principal pharmacological effects of (-)-Clau were to increase the cognition of mice/rats and inhibit, to different degrees, the pathological changes of AD through its multi-target effects [9,10]. Claulansine F (Clau F) is a new carbazole alkaloid isolated from the stem of C. lansium (Lour) Skeels [11].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring clausenamide is in racemic form, and like BRS-015, it acts as a LTP enhancer (Chu and Zhang, 2014; Chu et al, 2016; Xu et al, 2005). Both compounds are roughly equiactive with EC50 values in the range of 10–20 μM.…”
Section: Discussionmentioning
confidence: 99%
“…BRS–015 is structurally related to the excitotoxin – kainic acid, a potent AMPA/kainate receptor agonist, and to the natural product clausenamide extracted from the shrub Clausena lansium used in Chinese folk medicine. Clausenamide has been shown to enhance LTP (Feng et al, 2009) and is thought to possess anti–dementia properties (Chu and Zhang, 2014; Chu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(+)-Balasubramide is an eight-membered lactam compound extracted from the leaves of the Sri Lankan plant Clausena indica . Previous studies have shown that clausenamide, a biosynthetic precursor of balasubramide, has anti-apoptosis [ 16 ] and anti-neuroinflammation effects, acting as an oxygen free radical scavenger and AMPK activator [ 17 , 18 ]. We have previously demonstrated a central role of AMPK-STAT1 axis in vascular inflammation regulation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%